Análise geoecológica da paisagem de várzea na Amazônia central: um estudo estrutural e funcional no Paraná de Parintins-AM - Albuquerque, Carlossandro Carvalho de (2012)
Amazonia in the Brazilian territory is distributed along the length of the Amazon River in the east / west. In this area there are two kinds of natural environments that characterize the region: the floodplain, the fluvial plain flooded annually, and mainland, land above the level of the rivers which consist of vast expanses of plateaus and dips. The Amazonia floodplain varies in its landscape constitution that are products of the different natural conditions and different forms of human occupation. This research aimed to conduct an analysis geoecological landscape in lowland environments in the area of Paraná from Parintins in the city of Parintins-AM, assessing their contribution to sustainable regional development patterns. The central idea was to analyze the existing landscape in Central Amazonian floodplain, so that the parameters established in the construction of this analysis can serve as guidelines for future ecological-economic zoning and thus seek improvement in the quality of life of riverine. The research was supported on geosystems focus, as a benchmark for the integration of natural and socioeconomic components that form the landscape of the Paraná from Parintins floodplain. The methodology allowed the delineation of landscape units, identifying natural and socioeconomic characteristics, on a local scale. With the units identified and mapped could develop a proposal for use of the area, from the preparation of an environmental zoning. We established two levels of analysis for identification of geoecological units: the first level of order from geosystems, with three units and the second level in terms of geofacies, composed of ten units with distinct characteristics. It is noteworthy that the zoning proposed in this paper is a product of the researcher's perception about the legal grounds of zoning laws and guidelines set out in the government and the community's relationship with the environment in Paraná from Parintins floodplain. Due to the territorial dimension chosen for the research on the scale of geofacies, set up to Paraná from Parintins three (3) areas: Productive Use Zone (PUZ); Restricted Use Zone Community (RUZC) and the Full Environmental Preservation Area (FEPA). This study also presents recommendations to strengthen initiatives aimed at sustainable development of these areas.